Pengaruh Peradaban Islam Terhadap Barat - Yahdi, Muhammad (Al-Hikmah, 2012)
Islamic civilization was established base on the holy book that is contextually, socially, spritually perfect. The perfectness of its doctrin makes Islam easily accepted and developed rapidly through out the word. Islamic civilization came to Europe at the time of Islam and Moslem widely spread out, both in science and social aspect. Europe people wanted to stand out beyond the advanced reached by the Moslem in the East